Voltage-Gated Sodium Channel β1/β1B Subunits Regulate Cardiac Physiology and Pathophysiology - Edokobi, Nnamdi; Isom, Lori L. (Frontiers in Physiology, 2018)
Cardiac myocyte contraction is initiated by a set of intricately orchestrated electrical impulses, collectively known as action potentials. Voltage-gated sodium channels (NaVs) are responsible for the upstroke and propagation of action potentials in excitable cells, including cardiomyocytes. NaVs consist of a single, pore-forming α subunit and two different β subunits. The β subunits are multifunctional cell adhesion molecules and channel modulators that have cell type and subcellular domain specific functional effects. Variants in SCN1B, the gene encoding the Nav-β1 and -β1B subunits, are linked to atrial and ventricular arrhythmias, e.g. Brugada syndrome, as well as to the early infantile epileptic encephalopathy Dravet syndrome, all of which put patients at risk for sudden death. Evidence over the past two decades has demonstrated that Nav-β1/β1B subunits play critical roles in cardiac myocyte physiology, in which they regulate tetrodotoxin-resistant and –sensitive sodium currents, potassium currents, and calcium handling, and that Nav-β1/β1B subunit dysfunction generates substrates for arrhythmias. This review will highlight the role of Nav-β1/β1B subunits in cardiac physiology and pathophysiology.